Performance Management and the Stifling of Academic Freedom and Knowledge Production. Issue 1 (24th March 2016) - Morrish, Liz; Sauntson, Helen
Abstract: In an era of neoliberal reforms, academics in UK universities have become increasingly enmeshed in audit, particularly of research 'outputs'. Using the data of performance management and training documents, this paper analyses the role of discourse in redefining the meaning of research, and in colonizing a new kind of entrepreneurial, corporate academic. The new regime in universities is characterized by slippage between the audit and disciplinary functions of performance management. We conclude that academic freedom is unlikely to emerge from a system which demands compliance with a regime of unattainable targets and constant surveillance.